A GIS-ASSISTED OPTIMAL BAGHDAD METRO ROUTE SELECTION BASED ON MULTI CRITERIA DECISION MAKING - Ghani Ahmed, Namir; Moutaz Asmael, Noor (Journal of Engineering and Sustainable Development, 2015)
Baghdad City suffers from severe traffic congestion due to the rapid urban expansion and travel demand growth. Based on many studies, urban rail transit was proposed by experts and related transit agencies as an optimal solution to solve this problem. Accordingly, Baghdad metro route selection based on multi-criteria was proposed to be studied, evaluated, and searched in the present research. The methodology utilizes a GIS to prepare and analyze data. Data were analyzed using a two-stage multiple-criteria decision-making (MCDM) model which includes Analytical Hierarchal Process (AHP) and TOPSIS methods. Moreover, a Geographic Information System (GIS) was used to explore the various route alternatives. To select the best alternative, all alternatives were evaluated against the selected criteria. The weighting system is not only based on experts’ opinions but also includes a set of measures based on real data. Based on the outcomes of the present study, alternative route number 1 can be recognized to be the optimal route in the year 2014, and alternative route 2 is recommended to be adopted to meet the high travel demand requirement in the year 2035.